al-‘Anāṣīru ad-Dākhiliyyatu fī “al-Māl wa al-ḥub” Fi Qiṣṣah al-Qaṣīrah al-Muḍīl - Hudzaifi, Ahmad Dicka (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
This study aims to reveal the intrinsic elements short story